Dairy Goat Milk Production of Community in Besut, Terengganu, Malaysia - Ramli, Abdullah; Nurul Amalina, Mohamad Nasir; Wan Khadijah, Wan Embong (2018)
The objectives of this study were to determine goat milk production from two community farms (Farm A and Farm B) in Besut, Terengganu as well as to compare the dairy performance between origin of goats (UniSZA Saanen Dairy Goat and Community Goat). The does were hand-milked once a day in the morning and recorded. The results showed that milk production was insignificant (p > 0.05) between the two community farms. However, it was significantly different (p < 0.05) for individual does as well as different age groups of goats for both farms. The milk production between UniSZA Saanen Dairy Goat and Community Goat were insignificantly different (p > 0.05). In conclusion, milk production of the two community farms in Besut was influenced by the individual age of the goats, regardless of the origin of the goats within the district.